An Ideational Metafunction Analysis of Indonesian Presidential Candidate Speeches - Adi Sutrisno (Departement of Mathematics Education, 2024)
The problem in this research is what the discourse context and inferences are about the speeches of the Indonesian presidential candidates in 2024. The focus is on discussing Prabowo-Gibran's expressions in their orations. The aim of the research is to describe the context and inference of discourse Prabowo Subianto's speech on electronic media TEMPO.CO and CNBC Indonesia. The type of research is qualitative research using a descriptive approach. The data sources in this research were taken from electronic media Tempo.CO and CNBC Indonesia.The data analysis technique uses content analysis. The results of context research and discourse inference in Prabowo Subianto's speech are that Prabowo Subianto's speech as a whole contains the context and inference of campaigning, enthusiasm, readiness and optimism of the presidential candidate pair. and representatives, the winning team, supporters, and especially the entire Gerindra Party family, with persuasive speeches for get more support so you can achieve victory. Prabowo's expressions regarding his work program are still being monitored and are being questioned by the public.